Comparative Analysis and Harmonization of Pharmacopeial Quality Standards for Medicinal Oxygen in the State Pharmacopoeia of the Russian Federation - I. V. Klinkova; O. G. Kornilova; V. L. Bagirova (Regulatory Research and Medicine Evaluation, 2026)
INTRODUCTION . Medicinal oxygen is a vital medicinal product. The current General Pharmacopeial Monographs (GPM; in Russian, OFS) of the 15th edition of the State Pharmacopoeia of the Russian Federation (SP RF), regarding the control of impurities in medicinal gases, are excessively voluminous and duplicate the requirements of the Pharmacopeial Monographs (PM; in Russian, FS), which complicates their practical application. The standards require updating based on international harmonization, taking into account the national specifics of analytical control. AIM . To systematize and comparatively analyze global and national quality standards for medicinal oxygen to optimize the structure and content of the GPMs and PMs of the SP RF. MATERIALS AND METHODS . A comparative analysis of monographs from leading foreign pharmacopeias (European Pharmacopoeia [Ph. Eur.], United States Pharmacopeia [USP], Indian Pharmacopoeia [IP], Pharmacopoeia of the People’s Republic of China [ChP], Japanese Pharmacopoeia [JP], and State Pharmacopoeia of the Republic of Belarus [SP RB]) and draft GPMs/PMs of the 15th edition of the SP RF was conducted. The requirements for medicinal oxygen were evaluated depending on the production method (cryogenic rectification and short-cycle unheated adsorption). RESULTS. It was established that international pharmacopeias regulate the quality of medicinal oxygen regardless of the production method, relying on highly selective physicochemical methods. Discrepancies in the impurity limits between the USP, Ph. Eur., and IP were identified. The case for retaining gas chromatography in Russian practice, successfully implemented both in domestic production control and in control laboratories, has been substantiated, provided that the general approaches to describing methods in the GPMs are harmonized. CONCLUSIONS . A strategy differentiating methodological approaches was developed: the GPMs contain general testing principles, while the PMs specify the specific analytical parameters. Draft PMs for medicinal oxygen (93%, liquid, and compressed) have been prepared and approved, ensuring a balance between integration into international standards and retention of proven national competencies.